2017
DOI: 10.1002/2211-5463.12323
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in silico structural analysis of Gallus gallus protein arginine methyltransferase 4 (PRMT4)

Abstract: Protein arginine methyltransferase 4 ( PRMT 4) is an essential epigenetic regulator of fundamental and conserved processes during vertebrate development, such as pluripotency and differentiation. Surprisingly, PRMT 4 homologs have been identified in nearly all vertebrate classes except the avian genome. This raises the possibility that in birds PRMT 4 functions are taken over by other PRMT family members. Here, we revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Over 130 PRMT4 protein substrates have been identified and most of them contain proline-rich motifs [78]. Deletion of the PH domain of PRMT4 results in a global decrease in both the interaction of the PRMT4 with its substrates and methylation activities [78,79]. Interestingly, structural studies of PRMT4 revealed striking differences in the orientation of the N terminus upon AdoHcy binding (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Over 130 PRMT4 protein substrates have been identified and most of them contain proline-rich motifs [78]. Deletion of the PH domain of PRMT4 results in a global decrease in both the interaction of the PRMT4 with its substrates and methylation activities [78,79]. Interestingly, structural studies of PRMT4 revealed striking differences in the orientation of the N terminus upon AdoHcy binding (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro methylation assays were performed in the presence of radiolabeled SAM ( 14 C‐labeld methyl‐group) using recombinant GST‐tagged substrates and PRMT enzymes purified from bacteria or eukaryotic cells as described in (Hyllus et al, 2007; Berberich et al, 2017). Eluted GST‐tagged or Flag‐tagged PRMT enzymes or immunoprecipitated HA‐tagged PRMT5/Myc‐tagged MEP50 were incubated with substrates (either bead‐bound GST‐tagged proteins or histone H3, H4, or bulk histones from calf thymus; Sigma‐Aldrich) in the presence of [ 14 C‐methyl]‐S‐adenosyl‐methionine ( 14 C‐methyl‐SAM 20 µCi/ml; Perkin Elmer) for 1–2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines and reagents U2OS, HeLa, HEK293T, PaTu8988t, MiaPaCa-2, S2-007, and Panc1 cells were maintained in DMEM supplemented with 10% fetal calf serum (FCS, Gibco/BRL), 1% penicillin/streptomycin at 37°C and 5% CO 2 . Sf9 cells were cultured as described in (Berberich et al, 2017). Detailed information on cell culture reagents, manipulations, plasmids, and antibodies (including the generation of a-me-p14 ARF ) is supplied in the Appendix Supplementary Methods.…”
Section: Methodsmentioning
confidence: 99%
“…In chicken, PRMT1, PRMT4, PRMT5, and PRMT8 have recently been identified ( Berberich et al, 2017 ; Wang et al, 2017 ; Hu et al, 2023a , b ); however, PRMT2 and PRMT6 seem absent in chickens. As known, PRMT5 regulates the production of type I interferons ( IFNs ), impairing the host defenses against RNA/DNA virus infection in human ( Cui et al, 2020 ), but the role of chicken PRMT5 in the innate immune response remains unclear.…”
Section: Introductionmentioning
confidence: 99%